Training and Self-Rated Performance in the UAE Free Zones Context - Al Mazmi, Shaikha Ali (2012)
This dissertation study on “Training and Self-Rated Performance in the UAE Free Zones Context” revolves around the objective and aims toward exploring and validating the relationship between training and self-rated performance including the relationship between training and each of the six other important dimensions or areas for assessment on the individual employees’ work performance which include: “understanding of work duties”, “work skills”, “work enthusiasm”, “quality of work”, “quantity of work” and “readiness to innovate”. In order to achieve this main objective, the researcher successfully gathered and compiled a list of related literatures which comprised the literature review section in the dissertation. Afterwards, the second phase of the qualitative study was conducted which mainly involved a combination of descriptive and exploratory types of qualitative studies that included the floating of survey questionnaires (self-administered surveys and the conducting of a series of interviews (key informant interviews) among the chosen respondents. Four types of methods of analysis were used to validate and interpret the study results as compiled in the SPSS program utilized by the researcher. Among these methods of analysis included factor analysis, a specific test was used to check if the Training Scale is Uni-Dimensional or Multi-Dimensional; reliability test, a test used to check the reliability of Training Variable, Performance Variable, and the Performance Factors in the study; correlation test, a test used to check the level of the significance of the relationship between the variables and the factors; and finally, the regression test, a test used to examine the validity of the seven hypotheses of this dissertation paper. This dissertation study on “Training and Self-Rated Performance in the UAE Free zones Context” revolves around the objective or aim of exploring and validating the relationship between training and self-rated performance including the relationship between training and each of the six other important dimensions or areas for assessment on the individual employees’ work performance which include: “understanding of work duties”, “work skills”, “work enthusiasm”, “quality of work”, “quantity of work” and “readiness to innovate” where the final finding was that there is a significant relationship with each of the stated. This study was not to delve into the specific details on all the other training-related issues that both employers and employees encounter in the workplace as another research study has to be conducted in order to address that. This dissertation study was therefore limited only to exploring and validating whether or not there really is a positive relationship or link between training as a concept and self-rated performance as a concept. Many recommendations were presented in light of the research study that proposes rather strategies that will help to streamline and address a "performance gap" (learning needed to meet performance standards for a current task or job), "growth gap" (learning needed to achieve career goals) or "opportunity gap" (learning needed to qualify for an identified new job or role).